Biological aspects of Diopatra sp. (Onuphidae, Polychaeta) collected from mangrove habitats of Jeruklegi, Cilacap Regency - Eko Setio Wibowo; IGA Ayu Ratna Puspitasari; Atang Atang; Joko Pamungkas (Depik, 2022)
Diopatra species are members of the family Onuphidae (Polychaeta, Annelida) that are widely used as fishing bait. These tubicolous worms are common in particular mangrove areas of Cilacap. However, biological aspects of Diopatra sp. inhabiting the areas have not been studied. In the present work, we investigated several biological aspects of the worms, including the segment number, the body weight and the sex ratio, based on Diopatra samples collected from four mangrove habitats of Jeruklegi Village, Cilacap Regency, between June and July 2021. The results show that the average numbers of segments of Diopatra sp. obtained ranged from 195 to 216 segments, whereas the average body weights ranged from 2.03 to 3.12 g, and the average sex ratios ranged from 0.5 to 1.3. In general, the biological aspects of Diopatra sp. between sampling sites were relatively similar; this can be attributed to the similar environmental conditions at all sampling sites, including salinity (25–32 ppt), water temperature (30–32 oC), dissolved oxygen (6.4–8.8 ppm) and pH (7). While Diopatra worm farming is necessary so that local people do not rely on natural catch, a further taxonomic study is required to reveal the identity of this economically important local species.Keywords:Biological aspectDiopatraMangrove habitatPolychaetesTubicolous worms